Analisis Makna Leksikal dalam Karangan Deskripsi Siswa Kelas XI SMA Muhammadiyah 1 SurakartaTahun 2015/2016 - Rochani, Eriska Dewi; , Prof. Dr. Abdul Ngalim, M.Hum (2016)
This study aimed to describe the lexical meaning and form deviations in class XI student essay description SMA Muhammadiyah 1 Surakarta year 2015/2016. Type of this research is descriptive qualitative. Researchers studied the lexical meaning in essay description of class XI SMA Muhammadiyah 1 Surakarta year 2015/2016. Basic techniques in this study is a decisive element sorting technique or techniques PUP. Through the aggregated power can be seen in the lexical meaning of class XI student essay description SMA Muhammadiyah 1 Surakarta year 2015/2016. The results showed that the composition description of a class XI student of SMA Muhammadiyah 1 Surakarta has 24 lexical meaning. Irregularities in class XI student essay description SMA Muhammadiyah 1 Surakarta year 2015/2016 was found a spelling error on a student essay, namely the use of punctuation errors periods and commas, word usage, and the use of capital letters. Keywords: semantics, lexical, description.